Pengaruh Budaya Organisasi, Motivasi Kerja, Komunikasi Internal dan Lingkungan Kerja terhadap Kepuasan Kerja Karyawan pada PT. PLN (Persero) ULP Nganjuk - Aprilie Cahya Rizky Abadi; Ni Ketut Yulia Agustini (Trending: Jurnal Manajemen dan Ekonomi, 2026)
The purpose of this study is to determine the influence of organizational culture, work motivation, internal communication, and work environment on employee job satisfaction at PT. PLN (Persero) ULP Nganjuk. The independent variables in this study are Organizational Culture (X1), Work Motivation (X2), Internal Communication (X3), and Work Environment (X4), while the dependent variable is Job Satisfaction (Y). This study uses a quantitative method where this study emphasizes hypothesis testing, the data used must be measurable. The data sources used are primary and secondary data. Determination of the number of samples was carried out using a non-probability sampling method with a purposive sampling procedure. A sample of 100 respondents was selected, with the criteria being permanent employees who had worked for at least one year and were directly involved in operational, service, and administrative activities within the Nganjuk ULP work environment. Hypothesis testing was conducted using multiple linear regression analysis. The conclusions obtained in this study are that organizational culture does not significantly influence employee job satisfaction at PT. PLN (Persero) ULP Nganjuk. Work motivation does not significantly influence employee job satisfaction at PT. PLN (Persero) ULP Nganjuk. Internal communication does not significantly influence employee job satisfaction at PT. PLN (Persero) ULP Nganjuk. The work environment significantly influences employee job satisfaction at PT. PLN (Persero) ULP Nganjuk.